Pengaruh kesehatan dan keselamatan kerja (K3), dan insentif terhadap motivasi serta kinerja karyawan pada bagian produksi - Anthony Frans (Masyarakat, Kebudayaan dan Politik, 2015)
The human factor is an important factor in implementing vision, mission in achieving company target. Human resources aspect need to get more attention from the company. Example of consideration that was given by the company is the provision of Occupational Health and Safety (K3) to the employees. This research examines a hypothesis, known as explanatory research. The research purpose are to explaining and analyzing the effect of work safety to work motivation; effect of work health to work motivation; understanding and analyzing the effect of incentive to employee performance; and explaining and analyzing the effect of motivation to employee performance in CV. Intan Mandiri Pratam, Kupang. In this research, work motivation was set as intervening variable. Direct impact between (K3) and incentive to employee are higher compare to K3 and incentive to motivation as variable. This research found that K3 and incentive are more impactful to worker compare to motivation as variable.